Development of waterjet-assisted cassava peeler - Sumaria, Raymond G.; Tan, Daniel Leslie S. (Annals of Tropical Research, 2018)
The study aimed to develop a water jet-assisted cassava peeler and evaluate its technical performance in terms of peeling capacity, peeling efficiency, and tuber loss during peeling. Performance evaluation of the developed peeler included treatments which were the combinations of the three methods of peeling (use of circular nozzle, use of flat nozzle, and the manual peeling using a knife) and three diameter ranges of cassava roots (35 ± 5mm; 45 ± 5mm;55 ± 5mm). Results showed that the peeling capacity of the water jet-assisted peeler with circular nozzle was significantly higher than manual peeling but not significantly different to the water jet-assisted peeler with flat nozzle. The diameter of cassava roots used also significantly affected the peeling capacity of the different peeling methods; lower capacity for smaller diameter cassava roots and higher capacity for bigger diameter cassava roots.